Problems of introducing "e-learning" in educational institutions - Baydjanov, Maksudbek; Murodullaev, Bakhtiyor; Khodjaev, Nodir; Mukhamedjanova, Fotima; Mukhamedjanova, Zukhra (MMIT Proceedings, 2024)
This article is devoted to determining the role and place of elearning in organizing the educational process in an educational institution. The essence of the organization of e-learning, its content and organizational and pedagogical capabilities, the importance of its components are revealed.